Biennial Oscillation Of Indian Summer Monsoon And Global Surface Climate In The Present Decade - Menon, Arathy (2009)
The ENSO-monsoon system is known to have a biennial component. Here we show using high resolution satellite data, mainly daily rainfall and sea surface temperature (SST) from the Tropical Rainfall Measuring Mission (TRMM), and daily scatterometer surface winds from QuickSCAT, that there is a clear biennial oscillation (TBO) in summer monsoon rainfall over Central India – Bay of Bengal (Cl-BoB) and the far west Pacific in the period 1999-2005. Summer (JJAS) mean rainfall oscillates between high and low values in alternate years; the rainfall is high in the odd years 1999, 2001, 2003, and 2005, and low in even years 2000, 2002 and 2004. The amplitude of the oscillation is significant, as measured against the long term standard deviation of seasonal rain based on 1979-2005 Global Precipitation Climatology Project (GPCP) data. We find that the TBO in rainfall is associated with TBO of SST over the tropical Indian, west Pacific and Atlantic Oceans in different seasons. There is no TBO in east Pacific SST, and no strong El Nino in this period. The TBO of SST is related to change in evaporation due to TBO of surface wind speed. A TBO of the surface branch of the Walker circulation in the eastern Indian and western Pacific basins is clearest in the autumn season during 1999-2005. There is a clear relation between a large-amplitude TBO of winter surface air temperature over north Asia associated with TBO of the Arctic oscillation (AO), and the TBO of summer monsoon rainfall. High rainfall over CI-BoB lin summer is followed by a relatively high value of the AO Index, and warm air termperature over north Asia in the succeeding winter. The Inter Tropical Convergence Zone(ITCZ) over the central Pacific and Atlantic Oceans shift north by about two degrees when the northern hemisphere is warm, reminiscent of the behaviour of the climate system of ENSO, decadal and palaeoclimate time scales. In this thesis we document the biennial oscillation of monsoon rain and its spatial structure in the recent period, and its relation with ...